2016
DOI: 10.1097/scs.0000000000002950
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Strategy for the Intraorbital Foreign Bodies

Abstract: Early removal of foreign bodies in orbital region is usually preferred due to the risk of neurologic damage and other complications. Surgical removal is quite challenging for foreign bodies like wood. Magnets can be used for metallic bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…Systematic evaluation of the case is the most important principle. [1410] The incidence of associated eye injury may range from 0.7-10.8% if only severe injuries, such as vision loss, are included[61213] and up to 90.6% if the most minor injuries, such as subconjunctival hemorrhage, are included. [5]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Systematic evaluation of the case is the most important principle. [1410] The incidence of associated eye injury may range from 0.7-10.8% if only severe injuries, such as vision loss, are included[61213] and up to 90.6% if the most minor injuries, such as subconjunctival hemorrhage, are included. [5]…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating orbital injuries constitute between 30% and 50% of all orbital traumas;[1] within these cases, it has been found that one of every six patients presents with a foreign body. [23] These types of injuries deserve special consideration because they can cause eye damage, damage to the orbital structures, and even brain damage[34] and can lead to serious sequelae such as vision loss, which in turn can have medicolegal considerations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact number and location of the wooden fragments should be approximated through imaging studies as best as possible before surgery. Utmost care must be taken to prevent fragmentation of wood pieces during extraction, which can result in fragment retention, migration or late infection [10].…”
Section: Discussionmentioning
confidence: 99%